Clinical Effects of Topical Tacrolimus on Fox-Fordyce Disease - Hilal Kaya Erdoğan; Işıl Bulur; Zeliha Kaya (Hindawi Limited, 2015)
Fox-Fordyce Disease (FFD) is a rare, chronic, pruritic, inflammatory disorder of apocrine glands. It is characterized by dome-shaped, firm, discrete, skin-colored, and monomorphic perifollicular papules. The most common sites of involvement are axillae and anogenital and periareolar regions which are rich in apocrine sweat glands. Treatment is difficult. Topical, intralesional steroids, topical tretinoin, adapalene, clindamycin, benzoyl peroxide, oral contraceptives, isotretinoin, phototherapy, electrocauterisation, excision-liposuction and curettage, and fractional carbon dioxide laser are among the treatment options. In the literature, there are articles reporting beneficial effects of pimecrolimus in FFD. Nevertheless, there have not been any reports about the use of tacrolimus in FFD. We report two patients diagnosed with FFD by clinical and histopathologic examination and discussed therapeutic effects of topical tacrolimus on FFD in the light of literature.